Mapping the Rapid Decline of the Intertidal Wetlands of China Over the Past Half Century Based on Remote Sensing - Song, Song; Wu, Zhifeng; Wang, Yuefeng; Cao, Zheng; He, Zhenyu; Su, Yongsong (Frontiers in Earth Science, 2020)
Intertidal wetland, located at the interface of the continent and ocean, provides significant support to human society. With China being the largest developing country and the second-biggest economy in the world, the intertidal wetland along its coast has been exposed to climate change and over-exploitation for decades. Despite its ecological and economic significance, the distribution and variation of the intertidal wetland remains unknown. In this study, based on a multi-temporal remote sensing archive accumulated since the 1970s, we detected the dynamics of the intertidal wetland along China’s coast, at a spatial resolution of 30 m and a time interval of 20 years, over the course of four decades (1970s–2015). The main objectives of this study lie in (1) examining the distribution of and variation in intertidal wetland extent in temporal and spatial aspects; (2) identifying the main driving force of the intertidal wetland dynamics; and (3) making suggestions for future research and management. The results suggest that the extent of intertidal wetland declined substantially during the last four decades, from 7848 km2 in the 1970s, to 6017 km2 in 1995, and finally to 4895 km2 in 2015. On average, the intertidal wetland was 0.22 km in width along the coast, and about 40% of the extent of intertidal wetland was located along the Jiangsu and Shandong coast in 2015. Width shrinkage was detected to be primarily due to seaward migration of the intertidal wetland as a result of intensive land reclamation for tourism, communication, and transportation, as well as the fishery industry. This study improved our understanding of the vulnerable but valuable transition zone covered by intertidal wetland. A high priority should be given to intertidal wetland conservation and habitat reconstruction with a view to a sustainable future.